Psychological health, sleep quality, and coping styles to stress facing the COVID-19 in Wuhan, China - Fu, Wenning; Wang, Chao; Zou, Li; Guo, Yingying; Lu, Zuxun; Yan, Shijiao; Mao, Jing (Translational psychiatry, 2020)
To understand Wuhan residents’ psychological reactions to the COVID-19 epidemic and offer a reference point for interventions, an online questionnaire survey was conducted. It included the Disorder 7-Item Scale (GAD-7), the Patient Health Questionnaire 9-Item Scale (PHQ-9), Athens Insomnia Scale, and Simplified Coping Style Questionnaire. Categorical data were reported as numbers and percentages. Multivariate logistic regression models were used to evaluate the association between demographic factors and anxiety, depression, sleep disorder, and passive coping style. A total of 1242 Wuhan residents investigated, 27.5% had anxiety, 29.3% had depression, 30.0% had a sleep disorder, and 29.8% had a passive response to COVID-19. Being female was the risk factor for anxiety ( OR = 1.62) and sleep disorder ( OR = 1.36); being married was associated with anxiety ( OR = 1.75); having a monthly income between 1000 and 5000 CNY ( OR = 1.44, OR = 1.83, OR = 2.61) or >5000 CNY ( OR = 1.47, OR = 1.45, OR = 2.14) was a risk factor for anxiety, depression, and sleep disorder; not exercising ( OR = 1.45, OR = 1.71, OR = 1. 85, OR = 1.71) was a common risk factor for anxiety, depression, sleep disorder, and passive coping style; and having a higher education level (bachelor’s degree and above) ( OR = 1.40) was associated with having a sleep disorder. Wuhan residents’ psychological status and sleep quality were relatively poorer than they were before the COVID-19 epidemic; however, the rate of passive coping to stress was relatively higher.